![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a.
$(x-15).27=0$
$x-15=0:27=0$
$x=15+0=15$
b.
$23(42-x)=0$
$42-x=0$
$x=42$
c.
$(9x+2).3=60$
$9x+2=60:3=20$
$9x=18$
$x=2$
d.
$71+(26-3x):5=75$
$(26-3x):5=75-71=4$
$26-3x=4.5=20$
$3x=26-20=6$
$x=6:2=3$
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (x – 45).27 = 0
=> x - 45 = 0
=> x = 45
b) 23.(42- x) = 23
=> 42- x = 1
=> x = 41
c. 3x – 5=7
=> 3x = 12
=> x = 4
e. 15 – 5x=10
=> 5x = 5
=> x = 1
![](https://rs.olm.vn/images/avt/0.png?1311)
a)17-(12+13)
=17-25
=-8
b)2347-450-347-550
=(2347-347)-(450+550)
=2000-1000
=1000
c)(-71).(-175)-75.71
=71.(175-75)
=71.100
=7100
d)93.(27-100)+(-3)^3.93
=93.(27-100)+(-27).93
=93.((-27)+(-73))
=93.(-100)
=-9300
bài 2 :
a)x-15=-20
x=-20+15
x=-5
b)3x+27=6
3x=6-27
3x=-21
x=-21:3
x=-7
c)3.(x-1)+27=102
3.(x-1)=102-27
3.(x-1)=75
x-1=75:3
x-1=25
x=25+1
x=26
d)|x-6|.7-(-2)^2=-8+39
sory ,câu này mk ko làm đc
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a) Ta có: \(82-7\left(3x-4\right)=47\)
\(\Leftrightarrow82-21x+28-47=0\)
\(\Leftrightarrow-21x+63=0\)
\(\Leftrightarrow-21x=-63\)
hay x=3(nhận)
Vậy: x=3
b) Ta có: \(97+4\left(5x-7\right)=129\)
\(\Leftrightarrow97+20x-28-129=0\)
\(\Leftrightarrow20x-60=0\)
\(\Leftrightarrow20x=60\)
hay x=3(nhận)
Vậy: x=3
c) Ta có: \(\left(7x-13\right)\cdot27-12=15\)
\(\Leftrightarrow189x-351-12-15=0\)
\(\Leftrightarrow189x-378=0\)
\(\Leftrightarrow189x=378\)
hay x=2(nhận)
Vậy: x=2
d) Ta có: \(\left(2x+3\right)\cdot13+23=140\)
\(\Leftrightarrow26x+39+23-140=0\)
\(\Leftrightarrow26x-78=0\)
\(\Leftrightarrow26x=78\)
hay x=3(nhận)
Vậy: x=3
đ) Ta có: \(52x+8x-5x=70\)
\(\Leftrightarrow55x=70\)
\(\Leftrightarrow x=\frac{70}{55}\)(loại)
Vậy: x∈∅
e) Ta có: \(19x-3x-x=60\)
\(\Leftrightarrow15x=60\)
hay x=4(nhận)
Vậy: x=4
g) Ta có: \(7\left(3x+1\right)-5\left(3x+1\right)=74\)
\(\Leftrightarrow2\left(3x+1\right)=74\)
\(\Leftrightarrow3x+1=37\)
\(\Leftrightarrow3x=36\)
hay x=12(nhận)
Vậy: x=12
h) Ta có: \(5\left(3x-1\right)+7\left(3x-1\right)=96\)
\(\Leftrightarrow12\left(3x-1\right)=96\)
\(\Leftrightarrow3x-1=8\)
\(\Leftrightarrow3x=9\)
hay x=3(nhận)
Vậy: x=3
-27 + 5( x-7 ) = 23 - (71-3x)
-27 + 5( x-7 ) = 23 - 71 + 3x
5(x-7) - 3x = 23 - 71 + 27
5x - 35 - 3x = -21
x( 5-3 ) - 35 = -21
x.2 - 35 = -21
x.2 = -21 + 35
x.2 = 14
x = 7
Vậy x = 7
-27+5(x-7)=23-(71-3x)
=>-27+5x-35=23-71+3x
=>-27-35-23+71=3x-5x
=>-14=-2x
=>-2x=-14
=>x=-14:(-2)
=>x=7
Vậy x=7